Features of the epidemiological history of patients with Lyme borreliosis - R. F. Sayfullin; N. N. Zvereva; M. A. Sayfullin; S. V. Smetanina; E. V. Kardonova; O. V. Shamsheva (Детские инфекции (Москва))
In the treatment of Lyme borreliosis (LB), early diagnosis is a key component. The epidemiological history of the patient plays one of the leading roles in suspected borreliosis and at the same time is an important criterion for clinical diagnosis.Purpose. Analysis of epidemiological history data in outpatient cases of LB in Moscow.Material and methods. We conducted a retrospective, non-randomized, single-center cohort study, based on the analysis of data from 660 outpatient records of patients, referred by local physician with tick bite or suspicion of LB, and consulted by an infectious disease specialist on the basis of the Infectious clinical hospital No.1 in Moscow. For further analysis, patients were divided by age and the presence or absence of LB. Confirmation of LB was based on clinical and/or laboratory criteria using methods of enzyme immunoassay and immune blot.Results. We have updated the epidemiological features of the LB for Moscow, such as: the relative number of cases in the administrative districts of Moscow, places and seasonality of tick bites. Among children, compared with adults, cases of a tick bite without the development of LB was predominant, which must be taken into account in order to avoid overdiagnosis of LB. In patients with LB, an indication of the fact of tick bite in the anamnesis was much less common than going to its habitats.Conclusion. Our data clarify the epidemiological features of LB for residents of Moscow. In the absence of a history of indications of tick bite, an informative sign for clinical diagnosis is a visit to its habitats, including not only trips to wooded areas, but also to suburban areas and parks.